Catalyst-free pH-responsive chitosan-based dynamic covalent framework materials. (1st February 2023) - Mahaninia, Mohammad H.; Yan, Ning
Abstract: This study reports a first example of chitosan-based dynamic covalent framework materials successfully prepared through one-pot/ultrasonic-assisted amidation reaction via either citric acid (CA) or trimesic acid (TMA) as the linker unit under moderate conditions. Chitosan-based framework materials with residual carboxylic acid functional groups were obtained by tripodal cross-linking reactions without the need of any catalyst. The obtained materials were capable of bond exchange via neighboring group participation (NGP) effect within their dynamic covalent networks. It was demonstrated that the chitosan-based framework materials could undergo a dynamic transamidation reaction to exhibit self-healing characteristics. The structural properties of the synthesized dynamic covalent framework materials were controlled by the type and composition of the tripodal cross-linkers. This study showcased a novel approach to synthesize biodegradable, self-healing, pH-responsive, and selective mixed-dye adsorbent materials using chitosan as the building block. Graphical abstract: Unlabelled Image Highlights: Synthesizing chitosan-based dynamic covalent frameworks using tripodal cross-linkers. Dynamic covalent bond exchange takes place via transamidation. Catalyst-free amidation reaction of chitosan has achieved at moderate conditions. Chitosan-based dynamic covalent framework materials display selective dye uptake.